ANALISIS KALIBRASI SUHU DAN KEBISINGAN PADA INKUBATOR PERAWATAN MENGGUNAKAN METODE ECRI - Zulfahmi Zulfahmi; Hotromasari Dabukke (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2018)
Incubator is a very important tool in hospitals, especially for premature babies. Because this tool is very related to the safety and survival of the baby, periodic calibration is needed. The purpose of this research is to find out the calibration techniques and the calculation of uncertainty of the data resulting from temperature and noise measurements. The incubator calibration activity refers to the ECRI method 415-20010301-01. As the determination of the threshold value or test passing value is +- 1C for temperature and <-65 dBA for noise. The results obtained from the calibration and calculation are 31.89 +- 0.48 C for temperature and 44.7 +- 7.2 dBA for noise. From these results it was stated that the CHS-i1000 incubator was declared suitable for use.